Communicate Science in UNESCO Global Geopark - Patrocínio, Filipe (2020)
UNESCO territories are spaces of Education, Science and Culture, but also of Communication. Today, communication is an imperative of these territories, both as dissemination strategies and as a way of positioning in different development domains. In any case, knowing how to communicate its resources, differentiating elements or defining strategies, constitutes a competitive advantage that cannot be neglected at the present time. In other perspective, communication translates a strategy defined by the territories, visible in the way it communicates and in what is communicated. However, it’s not always easy to convey the values we want, much less when we speak about Science. The UNESCO Global Geoparks, as well-defined spaces where a community development strategy based on geology is built, are also areas of science. As such, communicating scientific knowledge, heritage resources, tangible and intangible values and culture itself are part of the daily life of a Geopark. Assuming the old maxim that we can only value what we know, the development of instruments, strategies and processes is fundamental, allowing the interpretation and dissemination of the geological heritage, but also of what is intended to be achieved with its valorisation, not only promoting greater attractiveness, but also a greater involvement of their communities, leading them to contribute in their own development. At Estrela Geopark, an aspirant to the UNESCO Global Geoparks network, communication plays a prominent role in its transverse development strategy. In each of its vital axes, tourism, science, education and sustainability, communication seeks to achieve three essential objectives: first, greater awareness of the Geopark brand and its own concept; secondly, greater dissemination of the territory; and thirdly, greater attractiveness, with more tourists, residents and investors. However, it`s not always easy to communicate science and scientific research. How to convey knowledge in an accessible, interesting and appealing way to the general public, whether visitors or residents? Aware of this difficulty, the Estrela Geopark betted early on interpretation as a central strategy for the whole communicative process. To interpret is the sine quo non condition for spreading knowledge, promoting geoconservation, achieving new forms of education and fostering our sense of belonging and pride. Throughout the last four years, several communication measures have been adopted, among which we highlight the "Portas do Geopark ", which are points of information and dissemination of heritage, and provide an entry into the territory. These "Portas" are the materialization of a dissemination strategy for the values of the Geopark throughout the 9 municipalities that compose this Aspiring with more than 2 thousand km2. Thus, 9 "Portas" and a tenth in the highest point of Continental Portugal, the Torre of Serra da Estrela, a place that receives approximately 2 million visitors per year, were created. In fact, communicating is much more than a simple way of transmitting knowledge, it`s a methodology that leverages the whole strategy of the Geopark, so that Estrela truly becomes a territory of Science, Education, Culture and Communication.